Building Teamwork in the Gotong royong Based Modern State: A Conceptual Investigation of Difficulties and Challenges - Gunardi Endro; Astrid Meilasari-Sugiana (Research Synergy Foundation Press, 2024)
It is difficult to contextualize the spirit of gotong royong that underlies communal life in ancient times to build modern teamwork. Questions arise about the incompatibility between gotong royong and modernity. This research aims to conceptually explore what underlies this incompatibility, how this incompatibility makes it difficult to build modern teamwork, and what solutions can be taken to overcome these difficulties. The traditional literature review method was chosen to achieve its objectives because the method provided flexibility to explore ideas, concepts, and insights from a variety of relevant literatures in various disciplines. Relevancy, comprehensiveness, and depth of conceptual assessment were used as criteria to select targeted literatures. The research results showed a sharp incompatibility, namely that gotong royong is characterized by a communal way of life whose principles are “giving” and “mutual giving,” while modernity is characterized by individualism, economism, and instrumentalism whose basic principles are “taking/having” and “mutual taking/having.” Sharp incompatibility is prone to producing a crisis of individual self-integrity and a culture of non-transparency, which in turn creates difficulties in building modern teamwork. A solution was proposed, namely, building self-integrity, which is conceptualized as a virtue acquired through identifying oneself with ideal communities (teams, organizations, social institutions, or human communities generally) of which one is a member. The self-integrity solution emphasizes individual aspects, places practical ethics at the center of the education system, and promotes ethical leadership.